2002
DOI: 10.1038/sj.cgt.7700397
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy with Apoptin induces regression of xenografted human hepatomas

Abstract: The chicken anemia virus-derived Apoptin protein shows remarkable specificity; namely, it induces apoptosis in tumor cells, but not in normal diploid cells. We have exploited the Apoptin gene for use in cancer gene therapy. Here we demonstrate that adenovirus-mediated intratumoral transfer and expression of the Apoptin gene results in regression or complete remission of human hepatomas grown as xenografts in immune-deficient mice, and significantly increases their survival long term. Early after intratumoral i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 22 publications
2
26
0
Order By: Relevance
“…Indeed, Apoptin induces apoptosis in vitro in actually all cancer cell types of a broad panel (470) that have been tested. 33 Previously, intratumoral treatment of hepatocarcinoma 9,11 or breast tumor 34 with recombinant Apoptin-expressing adenovirus vectors resulting in clear signs of tumor regression were reported. Recently, Guelen et al 6 and Maddika et al 35 have provided evidence that at least under in vitro conditions TAT-Apoptin protein can be transduced into human normal and tumor cells, resulting in induction of cell death in tumor cells only.…”
Section: Asor-apoptinmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Apoptin induces apoptosis in vitro in actually all cancer cell types of a broad panel (470) that have been tested. 33 Previously, intratumoral treatment of hepatocarcinoma 9,11 or breast tumor 34 with recombinant Apoptin-expressing adenovirus vectors resulting in clear signs of tumor regression were reported. Recently, Guelen et al 6 and Maddika et al 35 have provided evidence that at least under in vitro conditions TAT-Apoptin protein can be transduced into human normal and tumor cells, resulting in induction of cell death in tumor cells only.…”
Section: Asor-apoptinmentioning
confidence: 99%
“…2 The viral death effector Apoptin protein [3][4][5][6] induces apoptosis in various hepatocarcinoma-derived cells, [7][8][9] but not in human primary hepatocytes. 10 Van der Eb et al 11 demonstrated that adenovirus-mediated intratumoral transfer and expression of the Apoptin gene resulted in regression or complete remission of human hepatocarcinomas grown as xenografts in immune-deficient mice.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Apoptin represents a potential agent for the treatment of tumors that have lost their p53 status and are therefore refractory to many cancer therapies. Apoptin has shown efficacy in treating human xenografted tumors in mice and is currently being evaluated as a gene therapy agent to selectively destroy cancer cells (van der Eb et al 2002).The molecular mechanism by which Apoptin induces apoptosis is largely unknown. Several studies have demonstrated that nuclear localization of Apoptin is required for induction of apoptosis (Danen-Van Oorschot et al 2003;Guelen et al 2004), suggesting that the cellular target of Apoptin is a nuclear protein.…”
mentioning
confidence: 99%
“…Thus, Apoptin represents a potential agent for the treatment of tumors that have lost their p53 status and are therefore refractory to many cancer therapies. Apoptin has shown efficacy in treating human xenografted tumors in mice and is currently being evaluated as a gene therapy agent to selectively destroy cancer cells (van der Eb et al 2002).…”
mentioning
confidence: 99%
“…93 Regression of xenografted human hepatomas using the chicken anemia apoptin has been recently described. 94 Considering the vast complexity and potential of the apoptosis, it is obvious that the apoptotisinduced elimination of HCC will be frequently revisited in the future.…”
Section: Using Apoptosis To Program the Cell Deathmentioning
confidence: 99%